A BIOMIMETIC UNDERWATER ROBOT DIRECTION CHANGING ALGORITHMS (FUDMA JOURNAL OF SCIENCES, 2023)
The performance of the steady-turning while swimming, and sharp-turning motion algorithms of a biomimetic underwater robot in the form of a fish is presented in this work. The biological fish modelled is a Mackerel - Scomber scombrus. It’s motion patterns are precalculated and programmed into its firmware as an inflexible algorithm to save power consumption due to continuous motor position recalculations. The robot tail is a six segments plywood panels with vulcanized rubber acting as joints. This tail structure is driven by three remote-control servomotors (Futaba 3003) under the control of microcontroller (PIC18F4520). The algorithm for steady turning is derived steady swimming by introducing offset in the servomotor displacements about the midline of the robot. The algorithm for sharp turning treats the three servomotors as one and turn them simultaneously to left or right and restore them quickly into straight form, which allows the robot to turn at a tight corner. A 54cm turning radius was achieved with the steady turn while swimming. The sharp turn however works but requires several attempts before a proper reorientation was achieved in the desired direction.
Keywords: Biomimicry; Hyper-Redundant; Robotic fish; Swimming; Teleost sp.; Turning